2018
DOI: 10.1039/c7nj05032a
|View full text |Cite
|
Sign up to set email alerts
|

A new polyoxovanadate-based metal–organic framework: synthesis, structure and photo-/electro-catalytic properties

Abstract: A new polyoxovanadate-based metal–organic framework has been synthesized, which exhibits high-performance bifunctional photo-/electro-catalytic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 96 publications
0
7
0
1
Order By: Relevance
“…Li's group used a Cu-complex-based POVH material [Cu(Pz)](V 4 O 10 ) as an efficient electrocatalyst toward the oxidation of AA (the electrocatalytic efficiency (CAT) was calculated to be 208.3%). 65 Recently, Peng et al synthesized three Cu-complex-based POVH materials [Cu(pty)(V 2 O 6 )]·H 2 O, [Cu(pty)(V 2 O 6 )] and [Cu(tpy)(V 2 O 6 )] (pty = 4′-(4′′-pyridyl)-2,2′:6′,2′′-terpyridine, tpy = 2,2′:6′,2′′-terpyridine) (Fig. 14a).…”
Section: Povh Materials With O-bridging Metal–organic Complexesmentioning
confidence: 99%
“…Li's group used a Cu-complex-based POVH material [Cu(Pz)](V 4 O 10 ) as an efficient electrocatalyst toward the oxidation of AA (the electrocatalytic efficiency (CAT) was calculated to be 208.3%). 65 Recently, Peng et al synthesized three Cu-complex-based POVH materials [Cu(pty)(V 2 O 6 )]·H 2 O, [Cu(pty)(V 2 O 6 )] and [Cu(tpy)(V 2 O 6 )] (pty = 4′-(4′′-pyridyl)-2,2′:6′,2′′-terpyridine, tpy = 2,2′:6′,2′′-terpyridine) (Fig. 14a).…”
Section: Povh Materials With O-bridging Metal–organic Complexesmentioning
confidence: 99%
“…Most of the existing studies reported the incorporation of POVs as a solid into carbon paste electrodes, so that analyses of the reactivity and stability of the POV under electrochemical conditions is challenging [62] . In addition, the studies often targeted facile electrocatalytic processes, for example, the conversion of nitrite, bromate, iodate, or ascorbic acid [127–129] . In contrast, little has been reported on more challenging (proton‐coupled) multielectron reactions for small‐molecule activation (e.g.…”
Section: Outlook and Emerging Topicsmentioning
confidence: 99%
“…[62] In addition, the studies often targeted facile electrocatalytic processes,f or example,t he conversion of nitrite,bromate,iodate,orascorbic acid. [127][128][129] In contrast, little has been reported on more challenging (proton-coupled) multielectron reactions for small-molecule activation (e.g. H 2 ,O 2 ,CO 2 ,N 2 ).…”
Section: Emerging Themes In Pov Energy Researchmentioning
confidence: 99%
“…The isolated region E of Figure 5 where there is a low band gap cluster contains polyoxovanadate-based MOFs, some of which have already been investigated for their conductive and electrocatalytic properties (e.g. FEYCOE 135 , XEHYEP 136 ). Similarly, the nearby isolated region F contains molybdenum oxide-based frameworks (e.g.…”
Section: Dimensionality Reduction For Structure-property Analysismentioning
confidence: 99%